2004
DOI: 10.1089/1044549041474805
|View full text |Cite
|
Sign up to set email alerts
|

IL-5–Induced Eosinophils Suppress the Growth ofLeishmania amazonensis In Vivoand Kill PromastigotesIn Vitroin Response to Either IL-4 or IFN-γ

Abstract: In IL-5 transgenic mice (C3H/HeN-TgN(IL-5)-Imeg), in which 50% of peripheral blood leukocytes are eosinophils, the development of infection by Leishmania amazonensis was clearly suppressed. To determine mechanistically how this protozoan parasite is killed, we performed in vitro killing experiments. Either IL-4 or IFN-gamma effectively stimulated eosinophils to kill Leishmania amazonensis promastigotes, and most of the killing was inhibited by catalase but not by the NO inhibitor L-N5-(1-iminoethyl)-ornithine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…However, this level of eosinophils can be easily obtained by injecting IL-5 expressing plasmid followed by electropolation (Watanabe et al, 2004). This treatment of mice increased the level of eosinophils up to 50% of peripheral white blood cells and 30% of eosinophils were observed 3 weeks after electropolation.…”
Section: Fig 5 Continuedmentioning
confidence: 99%
“…However, this level of eosinophils can be easily obtained by injecting IL-5 expressing plasmid followed by electropolation (Watanabe et al, 2004). This treatment of mice increased the level of eosinophils up to 50% of peripheral white blood cells and 30% of eosinophils were observed 3 weeks after electropolation.…”
Section: Fig 5 Continuedmentioning
confidence: 99%
“…To examine the latter possibility, the IL-5 gene was introduced into murine muscles by electroporation to increase the eosinophil compartment. Using flow cytometric analysis, we defined the eosinophil compartment on the basis of its high forward and side scatters, as previously reported [11, 12]. We found that most of these cells expressed CD11b and F4/80.…”
Section: Discussionmentioning
confidence: 69%
“…Fourteen days later, the spleens were harvested and subjected to flow cytometric analysis. As previously reported [11, 12], cells with high levels of side scatter can be regarded as eosinophils. The splenocytes were incubated for 30 min on ice with FITC- or PE-labeled Abs at optimal concentrations and then washed with cold 2% FCS-PBS.…”
Section: Methodsmentioning
confidence: 76%
See 1 more Smart Citation
“…The splenocytes were then subjected to flow-cytometric analysis to evaluate their forward and side scatters. As previously shown,13 14 cells with high levels of side-scatter are considered to be eosinophils. Splenocytes were stained with FITC-labelled anti-CD3 (145-2C11), FITC-labelled anti-CD45R/B220 (RA3-6B2) or PE-labelled anti-F4/80 (A3-1) (Caltag Laboratories, Burlingame, California).…”
Section: Methodsmentioning
confidence: 91%